Tinjauan Geografi Regional terhadap Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI) - M. Baiquni (Universitas Muhammadiyah Surakarta, 2012)
Regional Geography at national level is a study of unique characteristics and pattern of natural phenomena and human phenomena in a certain region which are delineated and regionalized for certain purpose. In this perspective, Masterplan MP3EI was launched by since 2011 be analyzed on how its relations with backward regions and boundary regions. A critical review related to what is the concept behind and how are the strategies implement this program. The research methods are literature review, maps pattern analysis, and indent interview. The results of this research are (1) MP3EI is driven by economic growth strategy and lack of local politics involvement i.e. autonomy; (2) The economic corridor of MP3EI partly related to backward region and boundary region of Indonesia; (3) There are many challenges on how to implement MP3EI such as: integration foreign high investment with local economy, synergy to autonomy, preserve nature conservation area, and enrich cultural heritage of cultural diversity.